2018
DOI: 10.1017/aaq.2018.38
|View full text |Cite
|
Sign up to set email alerts
|

THE MICROBLADE INDUSTRY FROM SWAN POINT CULTURAL ZONE 4b: TECHNOLOGICAL AND CULTURAL IMPLICATIONS FROM THE EARLIEST HUMAN OCCUPATION IN ALASKA

Abstract: Swan Point in central Alaska contains the oldest recognized human occupation in Alaska (Cultural Zone 4b [CZ4b]), dating to circa 14,000 cal BP. This component consists of a microblade and burin industry with clear technological ties to the Siberian Upper Paleolithic Diuktai Culture. Through the systematic use of the Yubetsu method for the production of microblades, Swan Point is technologically more similar to Siberian microblade sites than to later-age (Denali complex) microblade sites in Alaska. The Yubetsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The ideal way to do so would be systematic refitting of chipped stone artifacts with the goal of searching for refits between components to determine to what extent items are moving vertically in these sites. There is a long tradition of such studies in archaeology, including Paleoindian archaeology both north and south of the ice sheets [ 39 , 42 , 46 , 80 85 ]. If little vertical distance separates refitting and conjoining artifacts, it might be shown that artifacts have not moved significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal way to do so would be systematic refitting of chipped stone artifacts with the goal of searching for refits between components to determine to what extent items are moving vertically in these sites. There is a long tradition of such studies in archaeology, including Paleoindian archaeology both north and south of the ice sheets [ 39 , 42 , 46 , 80 85 ]. If little vertical distance separates refitting and conjoining artifacts, it might be shown that artifacts have not moved significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The Swan Point archaeological site, in interior Alaska, has become a prominent fixture in discussions about terminal Pleistocene human colonization and migrations into Eastern Beringia (Alaska and Yukon) and the Americas from northeastern Asia. The site contains some of the earliest unequivocal evidence of occupation in northern North America and late Pleistocene connections to stone tool traditions in eastern Siberia and Japan (Potter et al 2017; Gómez Coutouly and Holmes 2018). Holmes and others (Holmes et al 1996; Holmes 2001; Potter et al 2014) previously reported that the earliest component, here referred to as a “Cultural Zone” (CZ), dates back to ∼14,000 cal BP.…”
Section: Introductionmentioning
confidence: 99%
“…Our test region consists of 7,000 km 2 of the valley of the Tanana River in central Alaska ( Fig 1 ). The study area contains a 14,500-year-long sequence of hunter-gatherer archaeological sites [ 23 , 24 ], many of which can be dated through radiocarbon or typological cross-dating. The region has experienced minimal disturbance by modern industry and, unlike many parts of the world, there is no overlay of agricultural settlements to obscure earlier hunter-gatherer sites.…”
Section: Introductionmentioning
confidence: 99%